2020
DOI: 10.1002/jcp.29997
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and physiological roles of Na+–K+–Cl cotransporter 2

Abstract: Na +-K +-Cl − cotransporter 2 (NKCC2; SLC12A1) is an integral membrane protein that comes as three splice variants and mediates the cotranslocation of Na + , K + , and Cl − ions through the apical membrane of the thick ascending loop of Henle (TALH). In doing so, and through the involvement of other ion transport systems, it allows this nephron segment to reclaim a large fraction of the ultrafiltered Na + , Cl − , Ca 2+ , Mg 2+ , and HCO 3 − loads. The functional relevance of NKCC2 in human is illustrated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 164 publications
(279 reference statements)
1
2
0
Order By: Relevance
“…NKCC2 is encoded by the Slc12a1 gene, located on chromosome 2, containing 29 exons with a full length of 77 kb. 26 Consistent with previous studies, CDK12 deficiency preferentially affects long genes with high numbers of exons. 5 It has been reported that CDK12 depletion decreases RNAPII CTD phosphorylation and lowers the RNAPII elongation rates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…NKCC2 is encoded by the Slc12a1 gene, located on chromosome 2, containing 29 exons with a full length of 77 kb. 26 Consistent with previous studies, CDK12 deficiency preferentially affects long genes with high numbers of exons. 5 It has been reported that CDK12 depletion decreases RNAPII CTD phosphorylation and lowers the RNAPII elongation rates.…”
Section: Discussionsupporting
confidence: 90%
“…NKCC2 mediates the cotranslocation of Na + , K + , and 2 Cl − ions through the apical membrane of TALs. 26 The major constituent of the osmotic gradient is NaCl. NaCl absorbed by NKCC2 enriches interstitial osmolality and fuels the countercurrent multiplication mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…22,54,55 Previous studies showed that differential splicing of NKCC2 pre-mRNA results in the formation of 3 functionally distinct isoforms, NKCC2A, NKCC2B, and NKCC2F that are important for the fine-tuning of TAL function. 14,15,56 Although little is known regarding the molecular mechanisms that regulate NKCC2 isoform expression, changes in salt conditions cause a shift in isoform expression in vivo and in vitro, possibly by altering NKCC2 pre-mRNA splicing as a means of adaptation in TAL cells. 33,57 While the high salt conditions used in the present study favor the induction of the NKCC2A isoform, 32 they also induce expression of both TNF and miR-195a-5p, which modulates the effects of high salt conditions on isoform expression.…”
Section: Discussionmentioning
confidence: 99%
“…NKCC2 inactivation causes the salt-losing Bartter syndrome. NKCC2 may be activated directly through increased surface expression and phosphorylation or indirectly through activation of renal outer medullary K + (ROMK) apical channels [ 50 ]. Uromodulin promotes phosphorylation of NKCC2 by SPAK (STE20/SPS1-related proline/alanine rich kinase) and OSR1 (oxidative stress response 1) kinases [ 16 ].…”
Section: An Overview Of Uromodulin Rolesmentioning
confidence: 99%